Blocking the Proliferation of Human Tumor Cell Lines by Peptidase Inhibitors from Bauhinia Seeds - Nakahata, Adriana Miti; Mayer, Barbara; Neth, Peter; Hansen, Daiane; Sampaio, Misako Uemura; Oliva, Maria Luiza Vilela (Planta Medica, 2013)
In cancer tumors, growth, invasion, and formation of metastasis at a secondary site play a pivotal role, participating in diverse processes in the development of the pathology, such as degradation of extracellular matrix. Bauhinia seeds contain relatively large quantities of peptidase inhibitors, and two Bauhinia inhibitors were obtained in a recombinant form from the Bauhinia bauhinioides species, B. bauhinoides cruzipain inhibitor, which is a cysteine and serine peptidase inhibitor, and B. bauhinioides kallikrein inhibitor, which is a serine peptidase inhibitor. While recombinant B. bauhinoides cruzipain inhibitor inhibits human neutrophil elastase cathepsin G and the cysteine proteinase cathepsin L, recombinant B. bauhinioides kallikrein inhibitor inhibits plasma kallikrein and plasmin. The effects of recombinant B. bauhinoides cruzipain inhibitor and recombinant B. bauhinioides kallikrein inhibitor on the viability of tumor cell lines with a distinct potential of growth from the same tissue were compared to those of the clinical cytotoxic drug 5-fluorouracil. At 12.5 µM concentration, recombinant B. bauhinoides cruzipain inhibitor and recombinant B. bauhinioides kallikrein inhibitor were more efficient than 5-fluorouracil in inhibiting MKN-28 and Hs746T (gastric), HCT116 and HT29 (colorectal), SkBr-3 and MCF-7 (breast), and THP-1 and K562 (leukemia) cell lines. Additionally, recombinant B. bauhinoides cruzipain inhibitor inhibited 40 % of the migration of Hs746T, the most invasive gastric cell line, while recombinant B. bauhinioides kallikrein inhibitor did not affect cell migration. Recombinant B. bauhinioides kallikrein inhibitor and recombinant B. bauhinoides cruzipain inhibitor, even at high doses, did not affect hMSC proliferation while 5-fluorouracil greatly reduced the proliferation rates of hMSCs. Therefore, both recombinant B. bauhinoides cruzipain inhibitor and recombinant B. bauhinioides kallikrein inhibitor might be considered for further studies to block peptidase activities in order to target specific peptidase-mediated growth and invasion characteristics of individual tumors, mainly in patients resistant to 5-fluorouracil chemotherapy.
Keywords: Bauhinia bauhinioides; Leguminosae; cancer; cathepsins; 5-FU; kallikrein; Kunitz inhibitors; trypsin inhibitor